Environmental DNA metabarcoding of fish and amphibian occurrence in created biodiversity wetlands in Uppland, Sweden - Kačergytė, Ineta (Swedish University of Agricultural Sciences, 2021)
The conducted study was done to determine the fish and amphibian occurrence patterns in created wetlands for biodiversity. The geographical study units were individual wetlands in Uppland, Sweden. For each wetland, the data contains all environmental variables considered and estimated within the study: Landscape forest within 1 km buffer, Size, Water vegetation, Flooded area, Year of creation, Connectivity to other wetlands. The data of amphibians and fish were obtained using environmental DNA metabarcoding, where a number of sequences were obtained. We report only whether the species eDNA was detected in a wetland or not (1/0).

Data: data contains fish and amphibian occurrence data in created wetlands in Uppland, Sweden.

Data collection description:
Fish and amphibian occurrence in 52 created biodiversity wetlands in Sweden determined by using environmental DNA metabarcoding from water samples. This took place during June and July year 2018.

The variables are described in detail in the documentation file.

A file with geographical coordinates for the wetlands can be found in the linked data repository, where Site_ID could be used as a common identifier.

A raw data file including the number of DNA reads can be provided upon request.

Studien utfördes för att undersöka förekomstmönster av fisk och groddjur i våtmarker anlagda för biologisk mångfald. Undersökningsområdet omfattade anlagda våtmarker i Uppland, Sverige. Data innehåller beskrivande miljövariabler: andel skog inom 1 km radie, våtmarkens storlek, andel vattenvegetation (t.ex. vass, kaveldun), area omgivande mark som översvämmas, anläggningsår, anslutning till andra vatten via vattendrag. Förekomstdata på fisk- och groddjursarter erhölls via vattenprov och eDNA analys. Här anges bara förekomst/icke förekomst av respektive art.

Data: Datat innehåller förekomstdata av fiskar och groddjur i anlagda våtmarker i Uppland.

Beskrivning av datainsamling:
Förekomst av olika arter fisk och groddjur i 52 anlagda våtmarker för biologisk mångfald i Sverige bestämdes genom att via vattenprover analysera rester av DNA i vattnet (sk. eDNA) för identifiering av arter. Det utfördes i juni och juli 2018.

Variablerna finns beskrivna i detalj i dokumentationsfilen

Ytterligare en datafil med geografiska koordinater för varje våtmark kan hittas i länkad dataförvaring, där ”Site ID” kan användas som en allmän markör för respektive våtmark.

En rådatafil, inkluderande antal läsningar DNA, kan fås vid förfrågan.
Miljö-DNA metastreckkodning av förekomst av fisk och amfibier i skapade biologiska mångfaldsmarker i Uppland, Sverige
Keywords: pond; damm; wetlands ecosystem; våtmarksekosystem; fishes; fisk; eDNA; eDNA; Environmental Sciences; Miljövetenskap; Ecology; Ekologi